Effect of a 12-Week Exercise Intervention on Anxiety and Depressive Symptoms Among Community Dwelling Older Adults - Kristrún Ólöf Sigurðardóttir 1986- (2014)
Evidence suggests that regular physical activity can be an effective treatment for people with symptoms of high anxiety and depression. The aim of this study was to examine the effect of a 12-week exercise intervention on anxiety and depressive symptoms among community-dwelling older adults from Reykjavík, Iceland. The participants were 27 (17 female, 10 male) older adults (mean age of 77.85±7.55). The main outcome included anxiety (GAD-7) and depressive symptoms (PHQ-9), measured before and after the 12-week exercise intervention. The exercise program consisted of a total of 24 exercise classes (40 minutes of low intensity aerobic/resistance training). An independent t-test, a paired samples t-test and a mixed two-way ANOVA were used to examine the changes in anxiety and depressive symptoms. At baseline there was no difference in anxiety and depressive symptoms between the exercise group and control group. After the intervention period, neither group showed any significant change in the level of anxiety and depressive symptoms (p > 0.05). The study is limited by a small sample size and high attrition rate. In the current study, we were not able to support the effectiveness of an exercise intervention for reduction of anxiety and depressive symptoms among older adults. Gögn hafa rennt stoðum undir gagnsemi reglulegrar líkamlegrar hreyfingar sem meðferðarúrræðis fyrir fólk sem sýnir einkenni mikils kvíða og þunglyndis. Markmið þessarar rannsóknar var að kanna áhrif líkamsræktar um 12 vikna skeið á kvíða- og þunglyndiseinkenni íbúa dvalarheimilis fyrir aldraða í Reykjavík. Þátttakendur voru 27 (17 konur og 10 karlar) aldraðir einstaklingar (meðalaldur 77,85±7,55 ár). Meðal helstu niðurstaðna voru mælingar á einkennum kvíða (GAD-7) og þunglyndis (PHQ-9) sem framkvæmdar voru fyrir 12 vikna æfingatímabilið annars vegar og að því loknu hins vegar. Æfingaáætlunin samanstóð af 24 tímum (hver og einn 40 mínútur af tiltölulega einfaldri þolþjálfun). Notast var við óháð t-próf, parað t-próf og blandað tvíhliða ...